Stick Figure and Think, Talk And Write: Integrating Media With Teaching Strategy For A Better Writing Competence - Eva Sudarwati; Shynta Amalia (IJER (Indonesian Journal of Educational Research), 2017)
Abstract This study attempts to see the effect of Think, Talk, and Write strategy on the students’ narrative writing competence. Considering the importance of the use of teaching media, this study tries to integrate Stick Figure as a teaching media in Think, Talk, and Write Strategy. A quasi experimental study was conducted to see the improvement of the students’ narrative writing competence. It involved 42 students who were selected on the basis of convenience sampling and assigned into two groups; experimental and control groups. The statistical analyses of paired sample t-test in experimental group showed that there was significant improvement on the students’ writing competence before (M=5.77, SD= 2.342) and after (M= 11.79, SD= 2.342), t(21)=12.059, p<0.05.Moreover, the result of independent t-test between experimental and control groups showed a significant difference. It can be seen that the mean differences was 3.79545 and the significance value is lower than 0.05, 0.000<0.05.